Reassessing Functional Differentiation and Dominus Litis Under Indonesia’s New Criminal Procedure Code - Huda, Chairul; Yulia, Rena; Romdoni, Muhamad; Saefudin, Yusuf; Ismail, Noorfajri (Jambe Law Journal, 2025)
The enactment of Indonesia’s Criminal Procedure Code 2025 (KUHAP 2025) marks the strengthening of the integrated criminal justice system, positioning the principle of functional differentiation as a primary tenet in the administration of criminal proceedings. Under its provisions, KUHAP 2025 clearly defines the authority of law enforcement institutions, ensuring that their respective functions are not encroached upon. However, the principle of dominus litis still places the prosecutor as the controller of the case, raising questions regarding the boundaries of authority between the fact-finding process conducted by investigators and the assessment of the appropriateness of prosecution. This study focuses on how the limits of investigative and prosecutorial authority within the KUHAP 2025 should be understood proportionally to ensure that the application of dominus litis does not obscure the neutrality of investigations. Clarifying these functional boundaries is essential to prevent the integrated criminal justice system from collapsing into one that conflates authorities, but functions as a cooperative framework that preserves objectivity in uncovering the truth. The study relies on the perspective of the KUHAP 2025, which promotes integration in the criminal justice system by differentiating – not unifying – authorities, allowing functions to complement and supervise one another. By distinguishing investigation as the discovery of factual guilt and prosecution as the evaluation of legal guilt, this research shows that functional differentiation and dominus litis are not opposing principles. Rather, they constitute complementary concepts necessary to avoid overlapping authorities in law enforcement practice.